(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted to investigate how the MOOC web OpenLearning was implemented in the process of learning writing skills among Year 3 TESL teacher trainees in UniversitiKebangsaan Malaysia.The researchers had carried out a case study approach for this study. Eight TESL trainees volunteered to participate in this study. Data was gained through three research tools which are open-ended questionnaire, focus group interviews and document analyses. The documents analyzed are respondents’ interactions in the comment section of OpenLearning and also WhatsApp.The findings of research question 1 are; a) Interactive features that help users to improve in writing, b) Friendly and easy to use platform, c) Abundance of subject-related materials provided. The findings of research question 2 are; a) Lack of lecturers’ feedback, b) Poor respondents’ engagement when completing tasks, c) Unstable Internet connection.The study implies that TESL teacher trainees will be best equipped with 21st Century teaching and learning skills highlighting the media literacy and technology literacy skills to become better future teachers.OpenLearning is used as one of the online mediums for tertiary students around the world to learn. It is an effort to transform the usual teaching and learning method to better suit the 21st Century kind of learning. In addition, the COVID-19 pandemic has also affected how tertiary students learn and to cope with this problem, integrating online learning such as OpenLearning is used more frequently.